加数、减数、被减数训练
加数、减数、被减数训练
加数、减数、被减数训练
被减数=减数+差
( )-8=7
( )-6=12
( )-7=6
( )—9=4
( )—7=4
( )-6=8
( )-5=7
( )—3=9
( )-4=12
( )-8=3
( )-7=5
( )-8=8
( )—7=7
( )—6=13
( )-6=9
( )-5=6
( )—12=7
( )-13=6
( )—11=9
( )—9=5
( )—14=5
( )—11=7
( )—12=8
( )-4=15
( )—8=12
( )—9=11
( )—1=15
( )—7=5
( )—8=6
( )—7=11
( )-12=6
( )—5=6
( )-13=4
( )-12=6
( )-15=2
( )—8=5
( )—9=7
( )—6=13
( )—8=7
( )-11=6
加数、减数、被减数训练
加数、减数、被减数训练
加数、减数、被减数训练
减数=被减数-差
加数、减数、被减数训练
加数、减数、被减数训练
加数、减数、被减数训练
15-( )=6
16-( )=5
18-( )=12
19-( )=11
13-( )=8
17—( )=4
15—( )=8
14-( )=9
18—( )=8
17-( )=10
13-( )=11
11-( )=7
12-( )=6
14-( )=7
18-( )=9
19-( )=11
11—( )=8
15-( )=4
13-( )=6
12-( )=3
11—( )=4
12-( )=8
16—( )=4
18-( )=3
17-( )=6
17-( )=8
14—( )=5
19-( )=13
13-( )=8
14—( )=4
12-( )=8
11-( )=9
13—( )=5
16-( )=4
17—( )=9
15-( )=6
14-( )=5
18-( )=3
14-( )=11
16—( )=8
加数、减数、被减数训练
加数、减数、被减数训练
加数、减数、被减数训练
加数=和—另一个加数
加数、减数、被减数训练
加数、减数、被减数训练
加数、减数、被减数训练
( )+8=12
( )+7=11
( )+11=18
( )+6=12
( )+8=14
( )+7=7
( )+9=15
( )+1=15
( )+6=14
( )+7=16
( )+3=15
( )+4=8
( )+6=7
( )+4=13
( )+7=18
( )+5=16
( )+7=13
( )+6=14
( )+8=13
加数、减数、被减数训练 来自淘豆网m.daumloan.com转载请标明出处.